СТАБИЛЬНОСТЬ СОВРЕМЕННЫХ АЛГОРИТМОВ ШИФРОВАНИЯ (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
This article is devoted to the analysis of modern data encryption algorithms. The introduction provides an overview of the most common encryption algorithms, such as AES and RSA. The main part of the article includes an analysis of the weaknesses of modern encryption algorithms and considers various attack methods. In general, it was concluded that the encryption algorithms used should be updated from time to time in order to apply complex methods of data protection and prevent possible attacks.